Delayed hemodialysis in COVID-19: Case series with literature review - Connerney, Michael (Clin Nephrol Case Stud, 2021)
Background: Increased incidence of kidney injury has been seen in patients with COVID-19. However, less is known about COVID-19 susceptibility and outcomes in end-stage renal disease (ESRD) patients on hemodialysis (HD). Reduced angiotensin-converting enzyme 2 (ACE-2) from SARS-CoV-2 binding and increased angiotensin II (Ang-II) activity have been suggested as mechanisms for COVID-19 renal pathophysiology. Materials and methods: In this case series, we analyzed the data of 3 patients with ESRD who had a delay in receiving their regular HD. Reduced oxygen requirement, resolved hyperkalemia, and normalized fluid status were used for the basis of discharge. Results: Presenting symptoms included fever, dyspnea, and dry cough. Laboratory markers were characteristic for COVID-19, such as lymphopenia, elevated D-dimer, C-reactive protein (CRP), and interleukin 6 (IL-6). All 3 of our reported patients required urgent HD upon admission. However, we report no fatalities in our case series, and our patients did not have a severe course of illness requiring endotracheal intubation. We reviewed COVID-19 pathophysiology and how patients with ESRD on HD may be particularly at risk for infection. Conclusion: New renal failure or ESRD sequelae, such as hyperkalemia, uremic encephalopathy, and fluid overload, can be exacerbated by a delay in receiving HD due to COVID-19 infection. Both direct COVID-19 infection and the challenges this pandemic creates to health care logistics present unique threats to ESRD patients on HD.